Lumbar Meningioma in a Dog - Auger, J. M.; Miller, C. W.; Smith-Maxie, L. L.; Bateman, K. E.; Duignan, P. J. (Veterinary and Comparative Orthopaedics and Traumatology, 1996)
Lameness may be the only detectable clinical sign in spinal meningiomas. An unusually young dog was diagnosed with lumbar meningioma whereas it had been referred for further evaluation of a previously treated partial anterior cruciate ligament rupture. Comparative aspects with the human counterpart are presented, showing prospects for improvement of treatment in the veterinary field.
Keywords: Lumbar meningioma; lameness; dog